Brooklyn crime novel - Lethem, Jonathan (Ecco, an imprint of HarperCollinsPublishers, 2023)
In the streets of 1970s Brooklyn, a daily ritual goes by the dance. Money is exchanged, belongings surrendered, power asserted. The promise of violence lies everywhere, a currency itself. For these children, Black, brown, and white, the street is a stage in shadow. And in the wings hide the other parents; cops; renovators; landlords; those who write the headlines, the histories, and laws; those who award this neighborhood its name. The rules appear obvious at first. But in memory's prism, criminals and victims may seem to trade places. The voices of the past may seem to rise and gather as if in harmony, then make war with one another. A street may seem to crack open and reveal what lies behind its glimmering façade. None who lived through it are ever permitted to forget.